Redeeming Wrath and Apocalyptic Violence: Girard and von Balthasar in Response to Nietzsche’s Critique of Atonement Theology - Poettcker, Grant M. (My University, 2013)
This dissertation compares the soteriologies of René Girard and Hans Urs von Balthasar as they engage and respond to the thought of Friedrich Nietzsche, and specifically, to Nietzsche’s critique of atonement theology. It examines a problematic shared by all three figures, one defined by the relationship between the violence and redemption. Chapter 1 traces the development of this problematic from Anselm through Luther and Calvin, and attends to the way changes in the metaphysical framework underlying the language of satisfaction led the Reformers to construe divine wrath in more strictly punitive terms. The subsequent chapters examine the responses offered by Nietzsche, Girard, and von Balthasar. Nietzsche argues that Christian priests used the event of Jesus’ violent crucifixion as a symbol to hold the weak in thrall; the Cross came to symbolize the threat of divine wrath and the hope of a quasi-magical salvation. Girard and von Balthasar each argue that Christian soteriology does not enslave Christians to a lie but orients all human beings to the truth. They also agree that the violence of the crucifixion is significant. But whereas Girard argues that the Christian doctrine of divine wrath is a residue of violent pagan religion and thus has no place in interpreting the meaning of the crucifixion, von Balthasar argues that this doctrine serves to highlight the unique quality of God’s re-ordering love. By analyzing and interpreting their responses to Nietzsche, this dissertation seeks to evaluate the contributions Girard and von Balthasar offer for a post-Nietzschean soteriology.
Keywords: Atonement; Theology; Nietzsche; Girard; von Balthasar; Violence; Religious Thought, Theology and Philosophy of Religion; Religious Thought, Theology and Philosophy of Religion